Enhancing ductility of sintered Fe-Ni-Mo-Mn-Si-C alloy by Co addition - Viseth Putsaccada; Jittraporn Wongsa-Ngam; Naoto Ohtake; Monnapas Morakotjinda; Rungtip Krataithong; Nattaya Tosangthum; Thanyaporn Yotkaew; Ruangdaj Tongsri (My University, 2024)
This research aims to investigate the effect of cobalt (Co) on accelerating the bainitic transformation in sintered Fe-Ni-Mo-Mn-Si-C alloys. Experimental sintered specimens were prepared from the mixtures of pre-alloyed Fe-4.00Ni-0.50Mo-0.2Mn powder with a fixed 4.00 wt% silicon carbide and varied Co contents (0.50 to 3.00 wt%) using a traditional press and sinter process. Sintering was conducted in a vacuum furnace at 1250 °C for 45 minutes and under slow cooling in the sintering furnace. It was found that Co strongly influenced the kinetics of bainite transformation in sintered Fe-Ni-Mo-Si-C-(Co) alloys. Tensile strength and hardness of sintered alloys increased with Co content. High elongation values were obtained in sintered specimens with high Co contents. The increases of tensile strength and ductility with Co content were attributed to accelerated bainitic ferrite formation and retained austenite stability, respectively.
Keywords: Ductility (Earth science); Elongation; Metal Alloys Wear and Properties